A Case of Chronic Gouty Arthritis with Atypical Localized Tophi - Samet Sancar Kaya; Mehmet Okcu (Galenos Yayinevi, 2018)
Gout disease is an inflammatory disease triggered by monosodium urate monohydrate crystals that accumulate in tissues due to hyperuricemia, which usually seen in males over 40 years. Chronic obstructive polyarthritis and chronic gouty arthritis coursing with tophi may develop in patients who are not adequately treated. Tophi are frequently observed in hand-foot fingers, olecranon bursa, prepatellar bursa, ear helix and achilles tendon. As for that in our case, tophi were present in bilateral lumbar paravertebral muscles and left cervical paravertebral muscles in addition to hand-foot joints, ear helix and olecranon bursa. In the patient who started colchicine 1 mg/day and allopurinol 300 mg/day, the joint pain improved and the tofus in the ear helix disappeared completely at the 6th month control. In conclusion, it should be kept in mind to clinical practice that in chronic cases, tophi may localized in atypical regions other than classical localizations, and tophus may lead to joint destruction due to delayed treatment.